2018
DOI: 10.1590/01047760201824042589
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOLOGICAL, ANATOMICAL AND PHYSIOLOGICAL CHARACTERISTICS OF Acrocarpus fraxinifolius WIGHT & ARN SEEDLINGS ACCORDING TO CONTAINERS AND FERTILIZATION

Abstract: Morphological, anatomical and physiological characteristics of Acrocarpus fraxinifolius Wight & Arn seedlings according to containers and fertilization. CERNE, v. 24, n. 4, p. 430-438, 2018. HIGHLIGHTS Acrocarpus fraxinifolius plants show increased growth and stem diameter when grown in 110 cm 3 tubes. Photosynthetic rate (A), stomatal conductance (gs) and transpiration (E) of Acrocarpus fraxinifolius in 110 cm³ tubes were similar to well-fertilized 50 cm³ tubes. The plants demonstrated expansion of Parenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In E. tereticornis seedlings, root restriction reduced biomass without affecting partition, and growth reduction was not well related to lower net leaf photosynthesis (Campany et al, 2017). While in Acrocarpus fraxinifolius Wight & Arn seedlings, stomatal conductance, net assimilation of carbon dioxide, transpiration, and quantum efficiency of photosystem II, depending on the fertilization they received, were reduced under smaller volumes of containers (Dias et al, 2018). In the same sense, Ouma (2007) observed that both the stomatal conductance and the net assimilation of carbon dioxide in M. indica seedlings were higher when produced in larger containers and more frequently irrigated.…”
Section: Effects Of Container Volumementioning
confidence: 87%
See 2 more Smart Citations
“…In E. tereticornis seedlings, root restriction reduced biomass without affecting partition, and growth reduction was not well related to lower net leaf photosynthesis (Campany et al, 2017). While in Acrocarpus fraxinifolius Wight & Arn seedlings, stomatal conductance, net assimilation of carbon dioxide, transpiration, and quantum efficiency of photosystem II, depending on the fertilization they received, were reduced under smaller volumes of containers (Dias et al, 2018). In the same sense, Ouma (2007) observed that both the stomatal conductance and the net assimilation of carbon dioxide in M. indica seedlings were higher when produced in larger containers and more frequently irrigated.…”
Section: Effects Of Container Volumementioning
confidence: 87%
“…Adequate supply of water for the seeds, without dormancy, associated with temperature and light are the main factors in the germination process (Taiz et al, 2017). However, the reduction in container volume can promote changes in seedling physiology (Ouma, 2007;Espinoza et al, 2017;Dias et al, 2018).…”
Section: Effects Of Container Volumementioning
confidence: 99%
See 1 more Smart Citation
“…Among the factors that influence the quality and production costs of seedlings of forest species, the nutritional demands of the species can be highlighted (Dias et al 2018). According to Pagliarini et al (2014), the need for fertilization stems from the fact that the substrate is not always able to provide all the nutrients that plants need for adequate growth.…”
Section: Introductionmentioning
confidence: 99%
“…Recipient volume also influences on the space occupied inside nursery, labor required to be handled, and transport, which determines the final production cost of seedling production (Stüpp et al, 2015). Seedlings production for both timber and ecosystem restoration purposes are limited to the lack of technical information on the seedlings' needs and correct chemical fertilizers and their precise doses (Rossa et al, 2015), as well as the recommendable recipient volumes to be employed (Dias et al, 2018). Thus, it is essential to carry out research and promote techniques to enable the production of native commercial species at low cost and adapted to the current planting systems.…”
Section: Introductionmentioning
confidence: 99%